Exploring the Risks Associated with Organisational Digitalisation in the Fourth Industrial Revolution: A Systematic Review - Elsabe Scholtz (African Journal of Inter-Multidisciplinary Studies, 2025)
The Fourth Industrial Revolution (4IR) ushered in the era of digitalisation, organisational transformation, and innovation of processes, strategies and operations. Integration of modern technology can provide opportunities for improvement, contributing to an organisation’s productivity and efficiency, but also introduces risks that may influence organisational performance and success. To effectively integrate 4IR technology into organisational processes and functions, organisations must understand the new risks and how they can be mitigated. Despite the growing need to embrace digitalisation, the lack of clear guidelines remains challenging. This paper aims to address the gap by developing a theoretical model that identifies the risks encountered during organisational digitalisation and contributes to literature and understanding of the digitalisation risks during 4IR. A systematic literature review was conducted using four recognised databases to highlight the leading risk types that organisations face during the digitalisation of their operations. Ten risk types were identified, and a model was developed to indicate the risk items within each type and the relationships between them. This paper emphasises the importance of understanding and managing risks and adopting a comprehensive risk management approach, allowing organisations to ensure sustainable success in the digital era of the 4IR.